Entrepreneurship, Structural Change and a Global Economic Crisis - Gries, Thomas; Naudé, Wim (Entrepreneurship Research Journal)

SME performance in transition economies: The financial regulation and firm level corruption nexus - Gries, Thomas; Wieneke, Axel (Journal of Comparative Economics)

Hardness and Non-Approximability of Bregman Clustering Problems. - Ackermann, Marcel R; Blömer, Johannes; Scholz, Christoph

How to Share a Secret - Blömer, Johannes (Algorithms Unplugged)

Solving the Closest Vector Problem with respect to Lp Norms - Blömer, Johannes; Naewe, Stefanie (arXiv:1104.3720)
In this paper, we present a deterministic algorithm for the closest vector problem for all l_p-norms, 1 < p < ∞, and all polyhedral norms, especially for the l_1-norm and the l_{∞}-norm. We achieve our results by introducing a new lattice problem, the lattice membership problem. We describe a deterministic algorithm for the lattice membership problem, which is a generalization of Lenstra's algorithm for integer programming. We also describe a polynomial time reduction from the closest vector problem to the lattice membership problem. This approach leads to a deterministic algorithm that solves the closest vector problem for all l_p-norms, 1 < p < ∞, in time p log_2 (r)^{O (1)} n^{(5/2+o(1))n} and for all polyhedral norms in time (s log_2 (r))^{O (1)} n^{(2+o(1))n}, where s is the number of constraints defining the polytope and r is an upper bound on the coefficients used to describe the convex body.

Income Determination and Income Discrimination in Shenzhen - Gries, Thomas; Gravemeyer, Stefan; Xue, Jinjun (Urban Studies)

Financial Deepening, Trade Openness and Economic Growth in Latin America and the Caribbean - Gries, Thomas; Kraft, Manfred; Meierrieks, Daniel (Applied Economics)

Causal Linkages Between Domestic Terrorism and Economic Growth - Gries, Thomas; Krieger, Tim; Meierrieks, Daniel (Defence and Peace Economics)

Interregional Migration, Self-selection and the Returns to Education in Brazil - Gries, Thomas; Kraft, Manfred; Piek, Christina (The Annals of Regional Science)

Short Signatures from Weaker Assumptions - Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike (Advances in Cryptology - ASIACRYPT 2011 - 17th International Conference on the Theory and Application of Cryptology and Information Security, Seoul, South Korea, December 4-8, 2011. Proceedings)